C41 AN UNUSUAL CASE OF "PULMONARY EMBOLISM". (18th May 2022) - Nannelli, C; Ferraro, N; Farsad, M; Cemin, R
Abstract: Background: Pulmonary vein stenosis (PVS) is a complication of catheter–based radiofrequency ablation (RFA) for atrial fibrillation (AF), caused by a vascular response which leads to replacement of necrotic myocardium with collagen. Clinical presentation can mimic pulmonary embolism (PE) and usually appears some months after procedure. Case report: A 65–year–old man was hospitalized in March 2021 with a complaint of worsening dyspnoea on exertion, over the course of one month. He had a past medical history of persistent atrial fibrillation, because of which he underwent four pulmonary vein ablations (both RFA and crioablation), the last one in 2019. The previous echocardiogram showed a high systolic pulmonary arterial pressure (sPAP of 75 + 5 mmHg) with normal right ventricular function and dimensions. Despite D–dimer at admission was negative, a CT pulmonary angiography was performed and showed occlusion of left superior pulmonary vein and a severe stenosis of right superior pulmonary vein; ventilation–perfusion scintigraphy (V/Q scan) demonstrated widespread decreased perfusion of both superior lung lobes. The patient underwent angioplasty of right pulmonary vein and after the procedure sPAP greatly decreased (35 mmHg). Discussion: Despite its reduction in incidence and its short–term presentation from procedure, severe symptomatic pulmonary vein stenosis must be considered among complications of ablation for atrial fibrillation. Delayed symptoms can also present years after procedure, even if in literature few similar cases are described. Ventilation–perfusion scintigraphy is a very sensible method to assess the functional significance of pulmonary vein stenosis and it also relates with symptoms' severity. It should be performed in case of a high clinical suspicion, considering that the characteristic ventilation–perfusion mismatch of this condition can be seen in other diseases too, over all pulmonary embolism. Conclusions: This case report emphasizes the importance of a thorough anamnesis and an exact interpretation of diagnostic imaging to correctly identify this AF ablation complication and optimize the patient's therapeutic management. It must be considered that PV stenosis can develop late and with unusual symptoms, mimicking other diseases, like pulmonary embolism, which has the same scintigraphic imaging.